2012
DOI: 10.1007/s12471-012-0361-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collaterals on deaths and re-infarctions in patients with coronary artery disease: a meta-analysis

Abstract: Background It is generally believed that there is a beneficial effect of collaterals on death and re-infarction statistics in patients with coronary artery disease (CAD) but studies to date are small and inconsistent. Objective To meta-analyse the studies published in this field in order to obtain more powerful information. Methods We searched Medline and major journals (2000 to 2011) for studies evaluating the effect of coronary collaterals on mortality. Publication bias, lack of heterogeneity, and lack of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Однако исследования, вошедшие в мета-анализ, включали как больных со стабильной ИБС, так и больных с острым ИМ [9].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Однако исследования, вошедшие в мета-анализ, включали как больных со стабильной ИБС, так и больных с острым ИМ [9].…”
Section: Discussionunclassified
“…Считается, что видимые при коронароангиогра-фии (КАГ) коллатерали ассоциированы с меньшей зоной инфаркта миокарда (ИМ) [5], лучшей сократи-мостью левого желудочка [6] и меньшей частотой сердечно-сосудистых осложнений в будущем как у пациентов с ИМ, так и со стабильной ИБС [7][8][9].…”
unclassified
See 1 more Smart Citation
“…A low CFI was associated with a higher mortality 18. Another, more recent meta-analysis by Akin et al confirmed these findings and showed that the presence of collaterals reduces mortality as well as re-infarction 19. However, a major limitation of both meta-analyses is the lack of adjustment for potential confounding variables.…”
Section: Collaterals and Survivalmentioning
confidence: 90%
“…Second, results are corrected for several important variables which may influence mortality in ACS. Previous studies, including meta-analyses,7 failed to adjust their findings for potential confounding factors. Indeed, after multivariable analysis, no significant difference was found in the present study by Meier et al between patients with and without collaterals in terms of 1-year mortality, MI and target vessel revascularisation.…”
mentioning
confidence: 99%